2022
DOI: 10.1039/d2fo00275b
|View full text |Cite
|
Sign up to set email alerts
|

Seventeen novel angiotensin converting enzyme (ACE) inhibitory peptides from the protein hydrolysate ofMytilus edulis: isolation, identification, molecular docking study, and protective function on HUVECs

Abstract: In the study, seventeen angiotensin converting enzyme (ACE) inhibitory peptides were isolated from protein hydrolysate of blue mussel (Mytilus edulis) and identified as MFR, MFV, FV, KP, QP, QVK, IK,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 67 publications
0
33
0
Order By: Relevance
“…The binding sites of Keap1 in the Kelch domain can be divided into five sub-pockets, namely P1 (Arg415, Ile461, Gly462, Phe478, Arg483 and Ser508), P2 (Ser363, Arg380, Asn382 and Asn414), P3 (Gly509, Ser555, Ala556, Gly571, Ser602 and Gly603), P4 (Tyr525, Gln530 and Tyr572), and P5 (Tyr334 and Phe577) [ 45 , 46 ]. Bioactive peptides bind to other macromolecular substances mainly through hydrogen bond force, van der Waals force and electrostatic interaction force, among which hydrogen bond force is the most important [ 27 , 47 ]. The molecular docking analysis indicated that the affinity of TCP3 with the middle cavity and bottom of Kelch domain was −7.4 kcal/mol and −6.6 kcal/mol, which was similar to those of TCP6 (−8.9 kcal/mol) and TCP9 (−8.5 kcal/mol) interacted with the middle cavity of Kelch domain.…”
Section: Resultsmentioning
confidence: 99%
“…The binding sites of Keap1 in the Kelch domain can be divided into five sub-pockets, namely P1 (Arg415, Ile461, Gly462, Phe478, Arg483 and Ser508), P2 (Ser363, Arg380, Asn382 and Asn414), P3 (Gly509, Ser555, Ala556, Gly571, Ser602 and Gly603), P4 (Tyr525, Gln530 and Tyr572), and P5 (Tyr334 and Phe577) [ 45 , 46 ]. Bioactive peptides bind to other macromolecular substances mainly through hydrogen bond force, van der Waals force and electrostatic interaction force, among which hydrogen bond force is the most important [ 27 , 47 ]. The molecular docking analysis indicated that the affinity of TCP3 with the middle cavity and bottom of Kelch domain was −7.4 kcal/mol and −6.6 kcal/mol, which was similar to those of TCP6 (−8.9 kcal/mol) and TCP9 (−8.5 kcal/mol) interacted with the middle cavity of Kelch domain.…”
Section: Resultsmentioning
confidence: 99%
“…Protein hydrolysates are complex mixtures of peptides with different molecular size and amino acid composition, which are the most critical factors affecting the separating and purifying process of BPs [ 4 , 20 ]. Therefore, ultrafiltration technology usually acts as a powerful technique to enrich APs with small MWs from various hydrolysates [ 21 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The findings were consistent with the results in existing literature that small MW AP fractions of protein hydrolysates from different marine resources, such as bluefin leatherjacket skins [ 19 ], monkfish muscle [ 21 ], blue mussel [ 45 ], skate cartilages [ 55 ], Antarctic krill [ 50 ], and tuna milts [ 33 ] and heads [ 39 ], had the strongest radical scavenging abilities. In addition, chromatographic methods, including ion exchange chromatography, gel permeation chromatography, and RP-HPLC, are generally applied to purify peptides from hydrolysate fractions depending on their acidity/basicity, molecular size, and adsorption affinities [ 1 , 4 ]. On these methods, 11 antioxidant peptides (TCP1–TCP11) were purified from protein hydrolysate of tuna cardiac arterial bulbs and presented significant antioxidant activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, ICY, LSFR, and IYSP could positively influence the production of nitric oxide (NO) and endothelin-(ET-) secretion in human umbilical vein endothelial cells (HUVECs) and weaken the adverse impact of norepinephrine (NE) on the production of NO and ET-. In addition, ICY, LSFR, and IYSP could provide significant protection to HUVECs against H O damage by increasing antioxidase levels to decrease Introduction Hypertension, also known as high blood pressure, is the most critical factor influencing the morbidity and mortality of cardiovascular disease (CVD) and renal disease (1)(2)(3). The prevalence of hypertension is about 1.3 billion, and this population may grow to 1.56 billion by 2030, which will cause a global economic burden of $274 billion (4).…”
mentioning
confidence: 99%